Fostering security of supply in contract-based preparedness in the public sector through the proactive contracting and legal design approaches - Kaave, Piia; Storsjö, Isabell (SAGE, 2026)
The article discusses the proactive contracting and legal design approaches and their role in enhancing contract-based preparedness and supply resilience in the public sector. It focuses on the impact of the COVID-19 pandemic on public procurement and supply chains, mainly in the healthcare sector in Finland. The pandemic exposed the need to prepare for unconventional threats and emphasized the importance of effective supply chain management. However, the classical legal approach and competitive tender mentality have dominated public procurement processes and contracts, limiting resilience and flexibility. Proactive contracting and legal design see contracts as multifaceted tools for preventing problems and promoting business success, and relationships. The article discusses tensions at the intersections of public procurement, supply resilience, proactive contracting and legal design approaches, and opportunities for enhancing contract-based preparedness. We argue that proactive contracting and legal design can complement Finland's comprehensive security approach by developing an organization's contracting and resilience capabilities to enhance contract-based preparedness.